Implementation of Public Services at The Semembang Village Office, Karimun Regency, In 2026 - Sanisah Sanisah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of public services in Semembang Village, Karimun Regency, in 2026. The research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. The research informants consisted of the Village Head, the Head of the Service Section, and members of the Semembang Village community, with a total of 13 informants. Data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of public services in Semembang Village has generally been carried out quite well based on the five dimensions of service quality, namely reliability, responsiveness, assurance, empathy, and tangibles. Village officials have provided services in accordance with established procedures, demonstrated friendliness and politeness, and made efforts to respond to the needs of the community effectively. However, several challenges remain, including administrative errors, delays in service delivery under certain conditions, limited service facilities and infrastructure, and accessibility constraints due to the geographical characteristics of Semembang Village as an archipelagic area. Nevertheless, the community generally expressed positive perceptions of the public services they received. The study concludes that the implementation of public services in Semembang Village has been generally satisfactory. However, further improvements are needed in enhancing the competence of village officials, upgrading service facilities, utilizing information technology, and developing service innovations capable of reaching all members of the community. These efforts are expected to improve the effectiveness, efficiency, and overall quality of public service delivery.